Chemistry of graphene oxide. Reactions with transition metal cations. (May 2017) - Amirov, Rustem R.; Shayimova, Julia; Nasirova, Zarina; Dimiev, Ayrat M.
Abstract: The main advantage of graphene oxide (GO) over its non-oxidized counterpart, is its ability to form stable solutions, due to exfoliation to single-atomic-layer sheets. At present day, the fine chemical structure of GO remains ambiguous, while the traditional characterization methods have exhausted their potentials in revealing GO chemistry. Here we employ the NMR relaxation method to monitor reactions between GO and the three transition metal cations Mn 2+, Gd 3+ and Fe 3+ while in solution phase. We demonstrate that interaction between GO and metal cations is chemical in its nature. The GO functional groups serve as ligands replacing water molecules from the metal cations' first coordination sphere. The functional groups interacting at different pH values have been identified and quantified. At least part of the functional groups interacting with metal cations in neutral and basic solutions are alcohols that have acidic character. The metal ion induced rearrangement of the oxygen functional groups on GO platform points at the highly dynamic nature of GO, confirming the main standing points of our earlier proposed Dynamic Structural Model. For Fe 3+, the polynuclear complexes with hydroxide ion bridges form on the surface of GO; the process of the seeding the nanoparticles on GO surface is recorded. Graphical abstract: